2020
DOI: 10.1128/aem.01204-20
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Resistance to a Glyphosate-Containing Herbicide in Salmonella enterica Does Not Result in a Sustained Activation of the Tolerance Response or Increased Cross-Tolerance and Cross-Resistance to Clinically Important Antibiotics

Abstract: Evolution of bacterial tolerance to antimicrobials precedes evolution of resistance and may result in cross-tolerance, cross-resistance or collateral sensitivity to other antibiotics. Transient exposure of gut bacteria to glyphosate, the world's most widely used herbicide, has been linked to the activation of the stress response and changes in susceptibility to antibiotics. In this study, we investigated whether a chronic exposure to a glyphosate-containing herbicide (GBH) results in resistance, a constitutive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…At the same time, MRIS is due to the over-expression of the mexAB-oprM efflux operon in clinical P. aeruginosa strains, while strains harbouring plasmid-mediated carbapenemase genes usually belong to the type III (IRMR) group 61 . In our study, we have discovered phenotypic imipenem resistance in parallel with meropenem and doripenem susceptibility in both clinical and environmental P. aeruginosa strains after co-exposure to antibiotics and GBHs, therefore, we presume, that the detected changes can be related to the porin regulation of oprD as it was described in the case of IRMS type strains 61 or to other general mechanisms against stressors 60 . The molecular mechanisms of the glyphosate and GBH-induced imipenem resistance in P. aeruginosa are yet to be investigated.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…At the same time, MRIS is due to the over-expression of the mexAB-oprM efflux operon in clinical P. aeruginosa strains, while strains harbouring plasmid-mediated carbapenemase genes usually belong to the type III (IRMR) group 61 . In our study, we have discovered phenotypic imipenem resistance in parallel with meropenem and doripenem susceptibility in both clinical and environmental P. aeruginosa strains after co-exposure to antibiotics and GBHs, therefore, we presume, that the detected changes can be related to the porin regulation of oprD as it was described in the case of IRMS type strains 61 or to other general mechanisms against stressors 60 . The molecular mechanisms of the glyphosate and GBH-induced imipenem resistance in P. aeruginosa are yet to be investigated.…”
Section: Discussionsupporting
confidence: 59%
“…The nonheritable resistance to antibiotics in E. coli induced by salicylates and other chemotactic repellents 59 , the kanamycin resistance of E. coli in the presence of GLY 26 and the kanamycin/ciprofloxacin resistance of S. Typhimurium induced by the exposure to Roundup 26 were previously reported. The imipenem resistance of P. aeruginosa induced by GLY and GBHs has a similar pattern and rapidity: therefore, it may be activated by an efflux or permeability-related mechanism as it was suggested in the case of E. coli 26 , or by the activation of general mechanisms against potential stressors, which does not necessarily require a change in the specifically targeted structures 60 .…”
Section: Discussionmentioning
confidence: 85%
“…A potential connection between glyphosate exposure, populations of pks + bacterial species such as E. coli and intestinal cancer development needs to be investigated (Davoren and Schiestle, 2018). Connections between glyphosate resistance in bacteria and antibiotic resistance also deserve more attention (Kurenbach et al, 2015;Kurenbach et al, 2018;Pöppe et al, 2020). As suggested by us earlier (van Bruggen et al, 2018), independent and trustworthy research is needed to revisit the tolerance thresholds for glyphosate residues in water, food and animal feed taking all possible health risks into account.…”
Section: Discussionmentioning
confidence: 98%
“…and other environmental bacteria (Kurenbach et al, 2015;Kurenbach et al, 2018;van Bruggen et al, 2018;Wicaksono et al, 2021). Other glyphosate resistance mechanisms have not been associated with antibiotic resistance (Pöppe et al, 2020).…”
Section: Glyphosate Effects On Microbial Communities In Soil Plants Animals and Humansmentioning
confidence: 99%
“…Data from the World Health Organization showed that some of the common resistant bacteria include Escherichia coli, Klebsiella pneumoniae , Salmonella spp., Streptococcus pneumoniae and Staphylococcus aureus are, in fact, common pathogens of both humans and livestock [ 55 ]. The situation is further complicated by the fact that resistance against a particular antibiotic group can offer cross-resistance to another antibiotic group [ 56 , 57 ]. Today, infections with antibiotic-resistant microorganisms lead to significant healthcare and economic losses, and are associated with extended hospital stays, higher mortality rates and greater risk of complications [ 58 , 59 , 60 ].…”
Section: Consequences Of Antibiotic Resistancementioning
confidence: 99%